2019
DOI: 10.1002/fam.2736
|View full text |Cite
|
Sign up to set email alerts
|

Engineering egress data considering pedestrians with reduced mobility

Abstract: Summary To quantify the evacuation process, evacuation practitioners use engineering egress data describing the occupant movement characteristics. These data are typically based to young and fit populations. However, the movement abilities of occupants who might be involved in evacuations are becoming more variable—with the building populations of today typically including increasing numbers of individuals: with impairments or who are otherwise elderly or generally less mobile. Thus, there will be an increasin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(14 citation statements)
references
References 90 publications
3
10
0
1
Order By: Relevance
“…Unimpeded movement speed of all participants was measured and analysed with respect to the individual abilities. Expected unimpeded movement speeds (1.47 ± 0.17 ms −1 ) were observed with the nondisabled reference population which is consistent with the literature [65]. Even slower unimpeded movement speeds were observed for the disabled populations, especially for the wheelchair users (0.96 ± 0.35 ms −1 ) and the mixed population (0.71 ± 0.26 ms −1 ).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Unimpeded movement speed of all participants was measured and analysed with respect to the individual abilities. Expected unimpeded movement speeds (1.47 ± 0.17 ms −1 ) were observed with the nondisabled reference population which is consistent with the literature [65]. Even slower unimpeded movement speeds were observed for the disabled populations, especially for the wheelchair users (0.96 ± 0.35 ms −1 ) and the mixed population (0.71 ± 0.26 ms −1 ).…”
Section: Discussionsupporting
confidence: 89%
“…Until now, only a few studies considered a more heterogeneous characterisation of participants. This challenge is addressed by a review of Geoerg et al [65] who discussed the influence of reduced mobility on characteristics of movement. Daamen et al [25,26] have performed movement studies with bottleneck configuration considering participants with disabilities.…”
Section: Introductionmentioning
confidence: 99%
“…This issue is particularly associated with physical exertion [33,63]. Obesity is common in developed countries, causing severe or complete loss of mobility [19,69].…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, people may have multiple impairments, and public buildings can often be very crowded, thus adding another layer of complexity to the specific evacuation needs of people with functional limitations. In crowded places, the evacuation performance of heterogeneous groups, including people with several functional limitations and able-bodied populations, will highly depend on the interactions between these groups and the space they are surrounded by [14,19,22]. In a study on the movement of heterogeneous groups trough bottlenecks, it is shown that the higher mixing ratios of wheelchair users and pedestrians affect the moving efficiency and increase congestion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation